Integrative Review on Silicone Breast Implants and ASIA Syndrome: What is the relationship? - Santos, Marco Aurélio Guidugli dos; Garcia, Elvio Bueno; Veiga, Daniela Francescato (Periódicos Brasil. Pesquisa Científica, 2024)
OBJECTIVE: The study aims to indicate the correlation between breast implants and the occurrence of ASIA Syndrome. METHODOLOGY: The articles were selected from the PubMed database, published between 2016 and 2021. The research used the Health Science Descriptors (DeCS) and their synonyms, in English: breast implants, silicones, autoimmune diseases and rheumatic diseases . RESULTS: Despite the divergent results between the studies analyzed, in most cases the correlation is evident between breast implants and the occurrence of autoimmune diseases. DISCUSSION: ASIA syndrome is involved as an adjuvant factor for the development of autoimmunity, as there is an exacerbation of the immunological response, with the release of cytokines and defense cells in the body with the presence of breast implants. The diagnosis is made based on the patient’s symptoms and past history, in which there are characteristic symptoms. The main treatment is the extraction of breast implants. There is an important correlation between low vitamin D levels and ASIA syndrome, in addition to the presence of other autoimmune diseases. CONCLUSION: Breast implants can be an adjuvant for the occurrence of ASIA syndrome, being reaffirmed by the improvement factors after silicone removal.